Global Crisis, Local Mysteries: Transcultural Echoes in the Contemporary Detective Narrative - Evita Badina (Baltic Journal of English Language, Literature and Culture)
The research examines the episode A Climate of Death from the British crime drama series Midsomer Murders (aired in December 2023), exploring how contemporary detective narratives integrate transcultural influences and ecological concerns. The study investigates the interplay of cultural diversity, environmental themes, and crime storytelling, using textual analysis as the primary method. Drawing on Wolfgang Welsch’s concept of transculturality alongside ecocritical and postmodern perspectives, the paper delves into the narrative strategies employed in this episode. By contrasting these elements with the more traditional frameworks of the Sherlock Holmes saga, the research highlights a shift in detective fiction – from reflecting Victorian-era cultural binaries to engaging with modern global anxieties. The study demonstrates that Midsomer Murders retains the genre’s foundational conventions while addressing contemporary societal challenges, creating a narrative space where local and global concerns converge.